Assessment of core and accessory genetic variation in Rhizobium leguminosarum symbiovar trifolii strains from diverse locations and host plants using PCR‐based methods. (1st August 2014) - Mauchline, T.H.; Hayat, R.; Roberts, R.; Powers, S.J.; Hirsch, P.R.
Abstract: The nitrogen‐fixing symbiosis between Rhizobium leguminosarum and host legumes is recognized as a key part of sustainable agriculture. A culture collection containing rhizobia isolated from legumes of economic importance in the UK and worldwide, maintained at Rothamsted Research for many years, provided material for this study. We aimed to develop and validate efficient molecular diagnostics to investigate whether the host plant or geographical location had a greater influence on the genetic diversity of rhizobial isolates, and the extent to which the core bacterial genome and the accessory symbiosis genes located on plasmids were affected. To achieve this, core housekeeping genes and those involved in symbiosis interactions were sequenced and compared with genome‐sequenced strains in the public domain. Results showed that some Rh. leguminosarum symbiovar trifolii strains nodulating clovers and Rh. leguminosarum sv. viciae strains nodulating peas and vicias shared identical housekeeping genes, clover nodule isolates from the same location could have divergent symbiosis genes, and others isolated on different continents could be very similar. This illustrates the likely co‐migration of rhizobia and their legume hosts when crops are planted in new areas and indicates that selective pressure may arise from both local conditions and crop host genotypes. Significance and Impact of the Study: The nitrogen‐fixing symbiosis between Rhizobium leguminosarum and host legumes has been recognized as a key part of sustainable agriculture for many years; this study provides new tools to study rhizobial biogeography which will be invaluable for extending the cultivation of legumes and indicating whether or not inoculation is necessary.